Effects of texture and grain size on mechanical properties of AZ80 magnesium alloys at lower temperatures. (5th January 2016) - Wang, Lifei; Mostaed, Ehsan; Cao, Xiaoqing; Huang, Guangsheng; Fabrizi, Alberto; Bonollo, Franco; Chi, Chengzhong; Vedani, Maurizio
Abstract: In order to investigate the effect of texture and grain size on mechanical properties of AZ80 magnesium alloy at lower temperatures, ECAP was conducted for 1, 2 and 4 passes at 523 K. Tensile and compressive tests were carried out on the ECAP processed samples at room temperature, 373 K and 423 K, respectively. The results showed that a significant grain refinement took place and the original extrusion fiber texture evolved into a new preferred crystal orientation, featuring a favorable alignment of the basal planes along shear planes after ECAP process. At room temperature grain refinement strengthening played an important role, leading to an improvement of mechanical properties with increasing number of ECAP passes. However, at higher temperature, texture and grain boundary sliding (GBS) mechanisms controlling deformation behaviors, resulting in a softening effect and considerable fracture elongation improvement, as well as yield asymmetry reduction. Graphical abstract: Highlights: The grain size is refined greatly and basal texture weakens by equal channel angular press (ECAP) on AZ80 magnesium alloys at 523 K. Grain size refinement plays an important role on the tensile/compressive deformation at room temperature, while grain boundary sliding, texture softening are much more important as temperature increases. Tensile/compressive asymmetry decreases after ECAP process and compressive yield strength exceeds tension as temperature increase on ECAPed samples.